#74: Development of a Solid-Organ Transplant-Specific Antibiogram in a Tertiary Pediatric Hospital in Canada. (26th March 2021) - Kitano, T; Science, M; Nalli, N; Timberlake, K; Allen, U; Campigotto, A
Abstract: Background: Solid-organ transplant (SOT) patients are more vulnerable to infections by antimicrobial-resistant organisms (AROs) because of their hospital exposure, compromised immune systems, and antimicrobial exposure. Therefore, it may be useful for transplant facilities to create transplant-specific antibiograms to direct empirical antimicrobial regimens and monitor trends in antimicrobial resistance. Methods: SOT (i.e., lung, liver, renal, and heart) antibiograms were created using antimicrobial susceptibility data on isolates from 2012 to 2018 at The Hospital for Sick Children, a tertiary pediatric hospital and transplant center in Toronto, Ontario. The Clinical Laboratory Standards Institute (CLSI) guidelines were followed to generate the antibiograms. The first clinical isolate of a species from a patient in each year was included irrespective of body site; duplicates were eliminated and surveillance cultures were excluded. Results from 2 years of data were pooled on a rolling basis to achieve an adequate sample size in both SOT and hospital-wide antibiogram. The SOT antibiogram was then compared with the hospital-wide antibiogram of the compatible 2 pooled years from 2012 to 2018. For subgroup analyses in the SOT population, organ-specific antibiograms and transplant timing-specific antibiograms (pretransplant, post-transplant <1 year, and post-transplant ≥1 year) between transplant and sample collection dates were analyzed. All proportions were compared using the χ  2 test. Results: The top 5 organisms in one (2 year) analysis period of the SOT antibiogram were Escherichia coli ( n = 29), Staphylococcus aureus ( n = 28), Pseudomonas aeruginosa ( n = 20), Enterobacter cloacae complex ( n = 18), and Klebsiella pneumoniae ( n = 17). For E.coli, susceptibility in the SOT antibiogram was significantly lower than those in the hospital-wide antibiogram in 2017/2018 for ampicillin (27% vs. 48%; P = 0.015), piperacillin/tazobactam (55% vs. 87%; P < 0.001), cefotaxime (59% vs. 88%; P < 0.001), ciprofloxacin (71% vs. 87%; P = 0.007) and cotrimoxazole (41% vs. 69%; P < 0.001), but not significantly different for gentamicin (94% vs. 91%; P = 0.490), tobramycin (88% vs. 90%; P = 0.701) and amikacin (100% vs. 99%; P = 0.558). These findings were consistent throughout the study period in E.coli . There was no statistically significant difference between the SOT and hospital-wide antibiograms for other organisms. There were no significant differences in susceptibility between organ-specific antibiograms or transplant timing-specific antibiograms in 2012–2018. Conclusions: We found that E.coli from the SOT population had a significantly lower sensitivity to all antimicrobials, except aminoglycosides, compared with those from the hospital-wide population. Other organisms had similar susceptibility to the hospital-wide population. Developing a SOT antibiogram will assist in revising and improving empiric treatment guidelines for this population.